Risk Factors Associated With Intradialytic Hypotension in Patients of End Stage Renal Disease on Maintenance Haemodialysis (Journal of Fatima Jinnah Medical University, 2018)
Introduction: Intradialytic hypotension is one of the most common complications to be observed during hemodialysis, occurring in about 15-20% of all sessions. The risk factors like interdialytic weight gain, UF rate, net ultrafiltration, pyrexia, food intake, cardiac events dialyzer type etc have been controlled due to modern hemodialysis equipments like hemodialysis machines with their better volumetric controls, sodium profiling, temperature control and patient counseling but still intradialytic hypotension is a major dialysis related complication.Objectives: Identify the risk factors responsible for intradialytic hypotension.Subjects and Methods: This cross-sectional study was comprised of one hundred patients of end stage renal disease carried out in the Department of Nephrology, Shaikh Zayed Hospital, Lahroe between 1st January 2010 to 31st March 2010. All adult patients on maintenance hemodialysis were included in this study. The patients on maintenance hemodialysis
Keywords: Intradialytic hypotension (IDH), dialysis sessions, ultrafiltration rate (UFR), interdialytic weight gain.